Evaluasi Pengaruh Media Tanam Sekam Bakar Dan Urine B2 Terhadap Pertumbuhan Dan Produktivitas Kacang Tanah - Tri Susanti Rahmadhani Nasution; Martirah Warni Zendrato; Nice Anjelin Gulo; Bridayanti Gea; Rahmad Winanda Telaumbanua; Yoel Melsaro Larosa (CV. SINAR HOWUHOWU, 2025)
This study aims to evaluate the effects of burnt rice husk growing media and B2 fermented urine as organic liquid fertilizer on the growth and productivity of peanut plants (Arachis hypogaea L.). The experiment was conducted using a Completely Randomized Design (CRD) with two factors: growing media (plain soil and soil + burnt rice husk) and B2 urine dosage (0 ml, 100 ml, and 200 ml). Observed parameters included plant height, number of leaves, number of pods, dry pod weight, and harvest index. The results showed that the combination of burnt rice husk and 200 ml of B2 urine significantly improved all growth and yield parameters. Burnt husk enhanced soil structure and pH, while B2 urine provided essential macro and micronutrients that accelerated plant development. In conclusion, the integration of burnt rice husk and B2 urine is effective in increasing peanut productivity and is a promising practice for sustainable agriculture systems.